Safety, pharmacokinetics, and pharmacodynamics of TV‐1380, a novel mutated butyrylcholinesterase treatment for cocaine addiction, after single and multiple intramuscular injections in healthy subjects. (12th January 2015) - Cohen‐Barak, Orit; Wildeman, Jacqueline; van de Wetering, Jeroen; Hettinga, Judith; Schuilenga‐Hut, Petra; Gross, Aviva; Clark, Shane; Bassan, Merav; Gilgun‐Sherki, Yossi; Mendzelevski, Boaz; Spiegelstein, Ofer
Abstract Human plasma butyrylcholinesterase (BChE) contributes to cocaine metabolism and has been considered for use in treating cocaine addiction and cocaine overdose. TV‐1380 is a recombinant protein composed of the mature form of human serum albumin fused at its amino terminus to the carboxy‐terminus of a truncated and mutated BChE. In preclinical studies, TV‐1380 has been shown to rapidly eliminate cocaine in the plasma thus forestalling entry of cocaine into the brain and heart. Two randomized, blinded phase I studies were conducted to evaluate the safety, pharmacokinetics, and pharmacodynamics of TV‐1380, following single and multiple administration in healthy subjects. TV‐1380 was found to be safe and well tolerated with a long half‐life (43–77 hours) and showed a dose‐proportional increase in systemic exposure. Consistent with preclinical results, the ex vivo cocaine hydrolysis, TV‐1380 activity clearly increased upon treatment in a dose‐dependent manner. In addition, there was a direct relationship between ex vivo cocaine hydrolysis (kel) and TV‐1380 serum concentrations. There was no evidence that TV‐1380 affected heart rate, the uncorrected QT interval, or the heart‐rate‐corrected QTcF interval. TV‐1380, therefore, offers a safe once‐weekly therapy to increase cocaine hydrolysis.